Secrecy Rate Analysis of mmWave MISO Ad Hoc Networks with Null Space Precoding - Darwesh, Ahmed F.; Fapojuwo, Abraham O. (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2020)
Secure communication in the millimeter wave (mmWave) network is an important issue in the next-generation wireless network due to the massive improvement in the eavesdroppers' ability. This paper studies the secrecy rate performance of a mmWave multi-input single-output (MISO) ad hoc network in the presence of colluding eavesdroppers. Firstly, to enhance the average achievable secrecy rate, an artificial noise (AN) transmission with null space linear precoder (Tx-ANLP) is applied, taking into consideration the effect of blockage and Nakagami fading. Consequently, the tools of stochastic geometry are used to derive the mathematical expression of the average achievable secrecy rate for mmWave MISO ad hoc network with Tx-ANLP technique. Numerical and simulation results show that, using the Tx-ANLP technique achieves more than three-fold improvement in the average secrecy rate over that without in the high power transmit regime (>15dBm). Moreover, the effect of increasing the colluding eavesdroppers' intensity without using the Tx-ANLP technique is studied which provides a high deterioration in the average secrecy rate. Conversely, when the Tx-ANLP technique is applied, increasing the colluding eavesdroppers' intensity has no negative impact on the secrecy rate. Furthermore, the proper power allocation between the message and AN signals which maximizes the average secrecy rate is computed. The results therefore show that the Tx-ANLP technique is a useful technique to enhance the secrecy performance of mmWave MISO ad hoc network in the presence of colluding eavesdroppers.